Platelets count and platelets indices; mean platelet volume and plateletcrit in pediatric chronic lung disease - Iman H. Draz; Iman A. Shaheen; Eman A. Youssef (SpringerOpen, 2020)
Abstract Background The lungs contribute in the final maturation of the circulating platelets, and some studies suggested that chronic lung disease (CLD) could impair circulating platelets maturation or count. Our aim was to study the validity of platelet count (PLT), mean platelet volume (MPV), and plateletcrit (PCT) as simple tools to assess chronic lung disease severity or predict its course. Results In 39 pediatric patients with CLD, we showed a significant rise in PLTs and PCT and a significant lower MPV when compared to normal controls (P values 0.003, 0.010, 0.004, respectively). Also, a significant positive correlation was detected between the C reactive protein (CRP) level and both the PLTs and PCT (r 0.327, 0.363 respectively) in addition to a significant reduction in MPV level in relation to the age of disease onset (P value 0.031). Conclusion This study disagrees with the postulation that chronic lung disease could lead to the reduction of circulating platelets and emphasizes the role of increased platelets count and decreased MPV in reflecting the inflammatory condition underlying the chronic lung disease in the pediatric age group.